Aplikasi Sistem Informasi Taman Pendidikan Al-Qur’an (TPA) Az-Zikra Berbasis Website Menggunakan Metode Rapid Application Development - Nurul Nikma Salsabila; John Socrates Kekenusa; Stephano Caesar Wenston Ngangi (Faculty of Mathematics and Natural Sciences Sam Ratulangi University, 2023)
In the modern era like now, the use of information technology has become an important part of daily activities. An information system is a system that processes data into information and websites as a medium for conveying information are very important. Az-Zikra Al-Qur'an Education Park (TPA) is a non-formal religious educational institution for the Muslim community which uses the Al-Qur'an as its main material, and to make the young generation Qur'anic and grounded in the Qur'an. . Located in Patampanua District, Pinrang Regency, South Sulawesi, and was founded in 2016. This place focuses on Muslim children aged 7-12 years. However, in managing data, TPA Az-zikra uses conventional methods. Recording of registrants, students, teachers, and TPA internal data is done manually, causing the data to be scattered and difficult to manage. Apart from that, the lack of efforts to disseminate information about TPA Az-zikra has also resulted in low public knowledge about this institution. To overcome this problem, researchers aim to create a website-based information system application using the rapid application development (RAD) method. This research produces a website-based information system application that can be used to make it easier for users to register as students at the Al-Qur'an Education Park (TPA) Az-zikra online, and at the Al-Qur'an Education Park (TPA) Az- zikra will make it easier to manage student data, teacher data and important information about the Az-zikra Al-Qur'an Education Park (TPA) so that it can be known by the outside community.